2016
DOI: 10.1016/j.ijdevneu.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Maternal separation prior to neonatal hypoxia‐ischemia: Impact on emotional aspects of behavior and markers of synaptic plasticity in hippocampus

Abstract:  We examined the interaction between MS and ΝΗΙ on emotionality and markers of plasticity. Both MS and NHI increased anxiety levels, but only NHI induced depressionlike behavior. Maternal separation did not further increase emotionality in HI-treated rats. Both MS and NHI decreased synaptophysin levels in dentate gyrus and CA3 hippocampal areas. BDNF expression in CA3 was decreased only in the HI animals that were maternally-separated. AbstractExposure to early-life stress is associated with long-term a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 136 publications
(187 reference statements)
1
23
0
Order By: Relevance
“…The present study re-examines FEs in individuals with ASD after accounting for impaired interoception (perception of the state of one’s own body). This is necessary due to recent claims of atypical interoception in ASD [ 8 12 ] and of a role for interoception in decision-making [ 13 , 14 ]. It was previously found that autistic 1 individuals are less susceptible to FEs because they do not incorporate emotional information into decision-making.…”
mentioning
confidence: 99%
“…The present study re-examines FEs in individuals with ASD after accounting for impaired interoception (perception of the state of one’s own body). This is necessary due to recent claims of atypical interoception in ASD [ 8 12 ] and of a role for interoception in decision-making [ 13 , 14 ]. It was previously found that autistic 1 individuals are less susceptible to FEs because they do not incorporate emotional information into decision-making.…”
mentioning
confidence: 99%
“…As demonstrated in Table 2 , although all questionnaires focus on the core construct of sensory processing, they did not all conceptualize this the same way. Therefore, in order to thoroughly assess an adult with ASD, it may be necessary and preferable to triangulate the results from multiple questionnaires, or to use different questionnaires depending on the purpose of the assessment [ 3 , 4 , 6 , 16 ]. For instance, some self-report measures (e.g., the SPQ) focus on assessing basic sensory perception.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, however, brain imaging may be utilized in combination with other assessment methods, to hone in on specific brain networks or structures to target to influence functioning. The clinical applicability of neuroimaging is likely to alter in the near future, as interventions that target neural or physiological processes such as repetitive transcranial magnetic stimulation, deep brain stimulation, medication/hormone therapy, desensitization therapy, and biofeedback applications become more commonly integrated with clinical practice [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations